Interfaces gráficas digitais em ambientes virtuais de aprendizagem: a usabilidade e experiência do usuário como fatores de melhoria no processo de ensino e aprendizagem - Mota, Darwin Rodrigues (2012)
This thesis aims to examine the structural concepts used to develop virtual learning environments, and link them to the Design field specifically concerning Usability and User Experience Design, in order to provide relevant information referring to the improvement of distance learning/education. The analysis of structural concepts comprehended in this thesis leads to questions previously tackled by theoreticians, especially Maria Elizabeth Bianconcini de Almeida and Andréa Filatro - whose works analyze the development of virtual learning environments -, and Jennifer Preece's et al, Jesse James Garret's, Jakob Nielsen's e Walter Cybis' works about the designing process, in other words, the project of interfaces that may allow providing effective information in the context of virtual learning environments. Product's quality and satisfactory yield are aspects co-related to the ease in using an equipment or program, and to the possibility of doing whatever the user's know how to do. Taking into account the expected results, the research was divided into three parts: a) graphic interfaces in which the historical context of user's graphic interface evolution is described -; b) usability and user experience design which will provide us with the methods and concepts used to analyze the interaction between user and informational system; c) and virtual learning environment which deals with the use of the mentioned tool for distance learning, and points out the interferences the instructional design and the interface design may cause during the conception process